Antifungal Activity of Endodontic Irrigants - Mohammadi, Zahed; Asgary, Saeed (Iranian Endodontic Journal, 2015)
Introduction: The purpose of this in vitro study was to assess the antifungal activity of final canal rinse with either three concentrations of sodium hypochlorite (NaOCl) (0.5, 2.6 and 6%), two concentrations of chlorhexidine (CHX) (2% and 0.2%), MTAD, Tetraclean, Hypoclean and Chlor-Xtra on Candida albicans (C. albicans) in a human tooth model. Methods and Materials: Two hundred and thirty five extracted human maxillary central and lateral incisors were used in this study. Teeth were randomly divided into nine test groups (n=25) and positive and a negative control groups (n=5). After cleaning and shaping, teeth were contaminated with C. albicans and incubated for 72 h. The irrigation solution in nine experimental groups included: 6% NaOCl, 2.6% NaOCl, 0.5% NaOCl, 2% CHX, 0.2% CHX, MTAD, Tetraclean, Hypoclean and Chlor-Xtra. After culturing on Sabouraud 4% dextrose agar, colony-forming units (CFU) were counted. Results: 6% NaOCl, 2% CHX and Chlor-Xtra were equally effective (P>0.05) and significantly superior to MTAD and Tetraclean (P<0.05). In addition, the effectiveness of Tetraclean and MTAD was significantly less than Hypoclean, NaOCl at all concentrations (6% 2.6% and 0.5%), MTAD and 0.2% CHX (P<0.05). Furthermore, Tetraclean was significantly more effective than MTAD (P<0.05). Conclusion: Antifungal activity of 6% NaOCl, Chlor-Xtra and 2% CHX was significantly greater than 2.6% NaOCl, 0.5% NaOCl, MTAD, 0.2% CHX and Tetraclean